Effects of drying methods on the drying kinetics and quality of maize - Chen, Pengxiao; Tian, Gaoshuai; Jiang, Mengmeng; Zhu, Wenxue; Wu, Jianzhang; Zhang, Runyang; Dai, Zhengzheng (International Journal of Agricultural and Biological Engineering, 2024)
At present, the maize is mostly dried by hot air, and the quality of maize after drying in this way is poor. So it is particularly important to explore the influence of new drying methods on the drying characteristics and quality of maize. Five drying methods, including hot air drying (HAD), vacuum drying (VD), infrared drying (IRD), variable temperature drying (VTD), and vacuum IR drying (VID), were used to analyze the drying rate (DR), moisture ratio (MR), effective moisture diffusion coefficient (Deff), hardness, nutrient composition, color, and microstructure of maize to investigate the effects of different drying methods on the drying kinetics and quality of maize kernels. The results showed that among the five drying methods, the modified Page drying model could most reflect moisture changes. VTD was better than the other methods in terms of DR, cracking rate, hardness, and crude fat. The highest lysine content in maize was obtained using HAD. The protein content was higher in IRD (p<0.05). The dough characteristics were better in VID and VTD than in IRD. The IRD, VTD, and VID-treated maize had a better color appearance. Microstructure analysis showed that the starch granules of VID, IRD, and VD-treated maize were oval but large gaps can be found between the granules. The granules were also densely stacked, with most of them relatively intact. Correlation and clustering analysis showed different degrees of correlation between the physicochemical indicators. The overall quality in VTD was the best, followed by VID, whereas HAD and VD showed poorer quality. In terms of economic value and product quality, VTD was the most suitable drying method for maize. This study can provide a theoretical basis for the application of maize drying in the processing industry. Keywords: maize, drying method, drying kinetics, quality, microstructureDOI: 10.25165/j.ijabe.20241705.8442Citation: Chen P X, Tian G S, Jiang M M, Zhu W X, Wu J Z, Zhang R Y, et al. Effects of drying methods on the drying kinetics and quality of maize. Int J Agric & Biol Eng, 2024; 17(5): 275-283.